Gaya Pidato Naratif MC Pada Acara Pernikahan Gaya Surakarta Dalam Industri Pernikahan - Dwijonagoro, Suwarna; Sukisno, Sukisno; Istikomah , Erna (Kamaya: Jurnal Ilmu Agama, 2025)
Since the Jatisari Agreement on Saturday, 15 February 1755, sectoral cultural legitimacy has occurred for the Kraton Surakarta Hadiningrat, including the holding of a Javanese wedding ceremony. The holding of the wedding ceremony is supported by the master of ceremony (MC/pewara) who is usually called pranatacara. This study focuses on the speech styles of the Javanese wedding ceremony attendants in the Surakarta style. Data sources were professional MC at the Surakarta style wedding ceremony (1) who came from Surakarta, totaling 3 people, and (2) who came from Surakarta but became MC in Yogyakarta, totaling 3 people. Data taken from youtube. Data validity with source triangulation and data saturation. Data were analyzed by stages of data selection, categorization, comparison, synthesis, and interpretation (McMillan & Schumacher, 2001). The results of the study show that the Surakarta style pewara has three speech styles, namely lamba songs, lamba rinengga songs, and candra songs. The style of speech is recorded in the form of audio and video. Patented research results that can be guided by the wardens. The results of the research were disseminated to PEPARI (Indonesian Pewara Association), PPY (Yogyakarta Pranatacara Association), and HARPI (Yogyakarta Association of Bridal Makeup Experts).